The Concept for Establishing Ideal Regional Regulations for Economic Improvement in Bone District - Nurdin; Djuniarti (Al-Daulah : Journal of Criminal Law and State Administration Law, 2022)
This study aims to determine whether regional regulations, especially local taxes and levies related to the local revenue of Bone City, have met the criteria for making good regional regulations. By looking at the principles of making Regional Regulations starting from the preparation stage of preparing the draft Regional Regulations to ratification and promulgation in the Regional Gazette of the City of Bone. The method used in writing this thesis is a normative study with an emphasis on a normative juridical approach, namely an approach based on legislation. The results of the study indicate that in order to produce a good Regional Regulation product that is in accordance with the demands of the community's needs, it is necessary to do it based on the procedures for the preparation of Regional Regulations to be more directed and coordinated. Regional regulations that regulate Regional Original Income (PAD) have not been oriented to the interests of the community. This is revealed in the research that in every consideration and general explanation of Regional Regulations, the expectation of the formation of Regional Regulations is to increase Regional Original Income (PAD), so that it seems that Regional Regulations regarding user fees tend to burden the community with various tariffs for which there is no clear standard of loading. Regional regulations are made based on the way of thinking that every public service must be charged with a number of tarifs, which should be a regional regulation as a means of regulation to provide convenience for the community in developing their business. Keywords: Regional Regulation; Economy; Local Government